Effect of Initial Cytoreductive Nephrectomy with Target Therapy versus Target Therapy Alone in Metastatic Renal Cell Carcinoma: A Single Institutional Study - Rasha Mohamed Abdel Latif; Kamel Farag Selim (Indonesian Journal of Cancer, 2019)
Background: The metastatic renal cell carcinoma (mRCC) patients treated with upfront cytoreductive nephrectomy (CN) combined with immunotherapy results in overall survival (OS) improvement. It is unclear whether mRCC patients treated with target therapy will also benefit from CN. The aim of the study was to identify the benefit of upfront CN followed by targeted therapy (TTs) versus TTs alone on OS of patients with mRCC, and to evaluate pre-operative variables for selection of patients who would benefit from CN, and also the response rate (RR) and the progression-free survival (PFS). Methods: A retrospective study was performed in our Department on patients diagnosed with mRCC within the period of January 2013 to April 2018. Data that were collected included patients and tumor characteristics. Patients were divided into two groups: 1) received upfront CN followed by TTs, and the 2) one treated with TTs alone. Survival analysis was performed using Kaplan-Meier method, univariate analysis with log-rank test was used to estimate predictors of survival in the CN group, and Cox regression was used for multivariate analysis. Results: The median OS of all patients was 14 months, and was 19 and 10.5 months in CN and non-CN respectively with significant difference (P˂0.001). Lower hemoglobin level (P=0.012), high neutrophil count (P˂0.001), low albumin level (P=0.006), number of metastatic sites ≥3 (P˂0.001), and patients with number of risk factors ≥3 (P˂0.001) have a negative impact on OS in CN group. Conclusions: Upfront CN before TTs in mRCC carries better survival than TTs alone. Five pre-operative variables (i.e. hemoglobin level, neutrophil count, albumin level, number of metastatic sites, and number of risk factors) were identified as suitable for selection of patients who will benefit from CN.